2005
DOI: 10.2460/ajvr.2005.66.432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the phospholamban gene in purebred large-breed dogs with dilated cardiomyopathy

Abstract: Results indicate that mutations in the phospholamban gene are not a frequent cause of DCM in Doberman Pinschers, Newfoundlands, and Great Danes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
0
6
1
1
Order By: Relevance
“…Phospholamban was investigated as a factor influencing DCM development in Newfoundlands, Great Danes, and Doberman Pinschers, but the results negated this possibility in these breeds (Stabej et al, 2005b). These results are in contrast with the data obtained by Lee et al (2009) who found a correlation between the down-regulation level of phospholamban and the severity of heart failure in dogs.…”
Section: Human Genetic Markers Of Heart Disease In Dogscontrasting
confidence: 58%
“…Phospholamban was investigated as a factor influencing DCM development in Newfoundlands, Great Danes, and Doberman Pinschers, but the results negated this possibility in these breeds (Stabej et al, 2005b). These results are in contrast with the data obtained by Lee et al (2009) who found a correlation between the down-regulation level of phospholamban and the severity of heart failure in dogs.…”
Section: Human Genetic Markers Of Heart Disease In Dogscontrasting
confidence: 58%
“…Evaluation of the desmin and delta sarcoglycan did not support a role for these genes in this disease 47,48 . In addition, the promoter and coding regions of the phospholamban gene and coding region of the actin gene have been excluded by comparison of direct sequencing results in affected and unaffected dogs 49,50 . However as more human disease variants are identified, the candidate gene approach will become increasingly fruitful for companion animal geneticists.…”
Section: Candidate Gene Approachesmentioning
confidence: 99%
“…DCM in Doberman Pinschers is a familial disease suspected to be inherited as an autosomal dominant trait 8 . The genes responsible for this condition remain to be identified, despite the fact that several candidate genes have been evaluated 1,8–10,16–18 . Extensive remodeling, in the form of a loss of collagen tethers, increased collagen synthesis, and alterations in collagen cross‐links, occurs in the diseased myocardium.…”
mentioning
confidence: 99%